Implementasi Metode CRISP-DM dalam Analisis Model Pendukung Keputusan Simple Additive Weighting dan Pengembangan Basis Data Riwayat Pembelian Layanan Akomodasi Hotel - Yerik Afrianto Singgalen (Universitas Budi Darma, 2023)
The development of studies on implementing Simple Additive Weighing (SAW) decision support models in purchasing hotel accommodation services or making stay decisions is limited to hotel recommendations calculated from consumer assessments of criteria with predetermined weights. However, it is necessary to develop a database with interactive visualization of hotel accommodation services and make it easier for consumers to compare and provide ratings. Considering this, this study uses the CRISP-DM method to develop a database based on the purchase history of hotel accommodation services in a business operational area, then uses SAW as a decision support model in the calculation process to produce the best hotel recommendations based on purchase data. The CRISP-DM method consists of business understanding, data understanding, modeling, evaluation, and deployment stages. At the business understanding stage,Â the customer's purchase history data is collected in the Agoda website review column. At the data understanding stage, the data collection process is carried out based on the supporting data of the criteria used. At the modeling stage, the SAW algorithm is used in the calculation process to get the best recommendations. In the Evaluation phase, hotels with the best recommendations are analyzed based on the guest's country of origin, guest sentiment, type of guest staying, room type used, length of stay, and month and year. In the Deployment stage, the database is developed using Oracle Apex and visualized interactively so that system users can understand consumer trends and behavior, especially in making overnight decisions based on purchase history data. Based on data obtained from the Agoda platform, it can be seen that A2 ranks first with a value weight of 0.983, then A3 ranks second with a value weight of 0.982, and A1 ranks third with a value weight of 0.946. Meanwhile, based on data obtained from the Booking.com platform, it can be seen that A3 ranks first with a value weight of 0.983, then A2 ranks second with a value weight of 0.974, and A1 ranks third with a value weight of 0.951. Thus, the SAW decision support model implementation output is not limited to the results of calculations and recommendation tables but includes a database with interactive visuals.